The lasting effects of historical racial divides in nursing education: A case study examining holistic admission policies development. (July 2022) - Houlahan, Bridget; Deveneau, Lilianna; Robinson, Jamie
Abstract: Background: Historically, in the United States, nursing programs reflected practices that systematically discriminated against Black students and nurses. Objectives: The authors investigated historical nursing school admission policies to determine if racist practices existed that impeded Black students' ability to access formal nurse training programs. This study further examined whether those historical discriminating practices continue to exist in schools of nursing today and if admission policies in a Southern School of Nursing contributed to inequitable admission of students. Current recommendations for increasing diversity, equity and inclusion in nursing schools will be addressed. Methods: This study combines social-historical archival research with a case study of the racial breakdown of applied versus admitted nursing students at a Southern university. Results: School of Nursing admission data (2019–2021) demonstrate discrepancies in the distribution of admitted students by race, reflecting the ongoing effects of systematic discrimination. Conclusions: In the United States, the nursing profession is pursuing strategies to promote diversity, equity, and inclusion. However, the lingering effects of policies that systematically built barriers keeping underrepresented groups from earning a nursing education persist. Holistic admission is one way that nursing programs can address this inequity. Highlights: Historical, racist practices still reduce opportunities for nursing students. Students of color have historically been denied access to nursing. Holistic admissions can help to close this educational achievement gap. A diverse and culturally competent nurse workforce is crucial for global health.